A call for more elaborate and transparent pension data to inform policy‐making: A critical examination of World Bank data for Eastern Europe. (April 2015) - Altiparmakov, Nikola
Abstract This article offers a critical analysis of the methods by means of which data relating to the performance of second pillar pension schemes are collated, compared and reported. This is done with regard to the performance of mandatory private second pillar pension funds in Eastern Europe. By critically examining data published in a number of World Bank studies, and through the identification of data problems and irregularities, the article argues that a much more elaborate and transparent approach to the collation, comparative analysis and reporting of data is needed. Required is the establishment of a consensus regarding what should represent a robust basis for making credible policy recommendations, not least with regard to pension re‐reforms in the countries of Eastern Europe and elsewhere. In the absence of such a consensus, unresolved data problems and irregularities may potentially continue to influence the formulation of incomplete national policy conclusions regarding the performance of second pillar pension funds and, in turn, the ability of policy‐makers to evaluate appropriately the need for, and assess the feasibility of implementing in a sustainable manner, pension re‐reform.